O prawnym charakterze obowiązku naprawienia szkody — uwagi na marginesie monografii Naprawienie szkody wyrządzonej przestępstwem Warszawa 2010 - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The author analyses the legal nature of the penal measure in the form of a legal obligation of remedy. The thesis that has so far been put forward in literature that it also fulfills penal functions raises considerable doubt. Relying on the views of A. Muszyńska, it can be concluded unambigously that the obligation of remedy ruled as an independent criminal reaction primarily serves compensatory purpose, preventative function in this case remains in the background.
Keywords: obligation of remedy; compensation/remedy; damages; crime